Food Safety: Thermochromic Latent‐Pigment‐Based Time–Temperature Indicators for Perishable Goods (Advanced Optical Materials 9/2015). Issue 9 (17th September 2015) - Galliani, Daniela; Mascheroni, Luca; Sassi, Mauro; Turrisi, Riccardo; Lorenzi, Roberto; Scaccabarozzi, Alberto; Stingelin, Natalie; Beverina, Luca
<x xml:space="preserve">Abstract</x> The image shows microcrystals of anilino‐squaraines, a strongly blue‐colored kind of pigment. The material can be obtained in the crystalline form by a temperature‐/time‐dependent treatment, starting from a colorless and amorphous precursor. The process is irreversible and easily detectable by the naked eye. On page 1164, L. Beverina and co‐workers describe how such materials can be used to prepare simple Time–Temperature integrators with applications in food safety.